Severe changes in thymic microenvironment in a chronic experimental model of paracoccidioidomycosis - Alves Da Costa, Thiago; Di Gangi, Rosária; Thomé, Rodolfo; Barreto Felisbino, Marina; Pires Bonfanti, Amanda; Lumi Watanabe Ishikawa, Larissa [UNESP]; Sartori, Alexandrina [UNESP]; Burger, Eva; Verinaud, Liana (Public Library of Science (PLoS), 2016)
T cell maturation takes place within the thymus, a primary lymphoid organ that is commonly targeted during infections. Previous studies showed that acute infection with Paracoccidioides brasiliensis (Pb), the causative agent of paracoccidioidomycosis (PCM), promotes thymic atrophy that is associated with the presence of yeast cells in the organ. However, as human PCM is a chronic infection, it is imperative to investigate the consequences of Pb infection over the thymic structure and function in chronic infection. In this sense, we developed a new experimental model where Pb yeast cells are injected through the intraperitoneal route and mice are evaluated over 120 days of infection. Thymuses were analyzed in chronically infected mice and we found that the thymus underwent extensive morphological alterations and severe infiltration of P. brasiliensis yeast cells. Further analyses showed an altered phenotype and function of thymocytes that are commonly found in peripheral mature T lymphocytes. We also observed activation of the NLRP3 inflammasome in the thymus. Our data provide new information on the severe changes observed in the thymic microenvironment in a model of PCM that more closely mimics the human infection.